The Influence of Work Environment, Work-life Balance, and Perceived Organizational Support on Employee Engagement - Rahmatunnisa; Hermin Endratno; Hengky Windhiandoni; Irawan Randikaparsa (Indonesian Journal of Business Analytics, 2025)
This study aims to analyze the influence of work environment, work-life balance, and perceived organizational support on employee engagement at Java Heritage Hotel Purwokerto. The research sample consisted of 110 employees of Java Heritage Hotel Purwokerto using purposive sampling technique. The results of the study indicate that work environment, work-life balance, and perceived organizational support have a significant effect on employee engagement. The results of this study provide important contributions to hotel industry management in understanding the factors that can increase employee engagement. Therefore, companies need to create a conducive work environment, support a balance between personal and professional life, and demonstrate a commitment to their employees' well-being.